Loop quantum gravity on dynamical lattice and improved cosmological effective dynamics with inflaton - Han, Muxin; Liu, Hongguang (Physical Review D, 2021)
In the path integral formulation of the reduced phase space loop quantum gravity (LQG), we propose a new approach to allow the spatial cubic lattice (graph) to change dynamically in the physical time evolution. The equations of motion of the path integral derive the effective dynamics of cosmology from the full LQG, when we focus on solutions with homogeneous and isotropic symmetry. The resulting cosmological effective dynamics with the dynamical lattice improves the effective dynamics obtained earlier from the path integral with a fixed spatial lattice: The improved effective dynamics recovers the Friedmann-Lemaître-Robertson-Walker cosmology at low energy density and resolves the big-bang singularity with a bounce. The critical density ρc at the bounce is Planckian ρc∼Δ-1, where Δ is a Planckian area serving as a certain UV cutoff of the effective theory. The effective dynamics gives the unsymmetric bounce and has the de Sitter (dS) spacetime in the past of the bounce. The cosmological constant Λeff of the dS spacetime is eme
CRIS-Team Scopus Importer:2021-07-16